The National Career Development Guidelines. Local Handbook for Middle Junior High Schools. - Northwest Regional Educational Lab., Portland, OR.; Northwest Regional Educational Lab., Portland, OR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This handbook, one of five local handbooks developed to support specialized implementation of the National Career Development Guidelines, presents guidelines for developing comprehensive programs for students in middle and junior high schools. Part I describes the need for guidelines and standards in career development, defines career development programs within the context of comprehensive educational programs, and discusses national, state, and local roles in establishing and implementing standards. A comprehensive set of student competencies and indicators is recommended and organized into three broad areas: self-knowledge, educational and occupational exploration, and career planning. An organizational capabilities section provides statements of the commitments, structure, and support required for effective career development programs. The personnel requirements section describes the roles of various staff members and identifies specific competencies needed by counselors and other staff for effective program delivery. Part II present an implementation process that uses the guidelines to establish career development standards and improve existing programs. The process encourages flexibility in standards-setting efforts, builds upon existing program strengths, stimulates coordination within institutions, and enhances cooperation with other organizations. Appendices provide a set of competencies and indicators for all levels; sample forms; local program examples; a listing of resource materials related to career development standards and program implementation; and a listing of all State Occupational Information Coordinating Committees. (NB)
Sponsoring Agency: National Occupational Information Coordinating Committee (DOL/ETA), Washington, DC.
ERIC Note: For other handbooks in this series, see CG 022 382-388.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Development; Career Planning; Junior High School Students; Junior High Schools; Middle Schools; Program Improvement; Standard Setting; Student Development; Student Needs; Guides, Non-Classroom.